Cover Picture: Plasma Process. Polym. 3∕2017. Issue 3 (March 2017) - Boselli, Marco; Chiavari, Cristina; Colombo, Vittorio; Gherardi, Matteo; Martini, Carla; Rotundo, Fabio
Abstract : Front Cover: Two different atmospheric pressure non‐thermal plasmas have been used to clean the surface of a corroded 19 th century daguerreotype. The figures on top show the figure visage untreated; after 2 nd plasma‐jet treatment on the left half‐side only; and after DBD‐plasma treatment of the right half‐side too. The figures at the bottom show optical micrographies in white light of the woman's eye on the left daguerreotype portion in (a) untreated conditions and (b) after plasma‐jet treatment. Further details can be found in the article by M. Boselli et al. on1600027 .